Portrait of Mary and Manggarai Women in “Dere Serani”: The Encounter of Religion and Culture - Widyawati, Fransiska; Dangku, Yohanes Mariano; Lon, Yohanes Servatius (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Catholics hold Mary, the mother of Jesus, in high esteem. The widespread presence of Marian devotions, teachings, dogmas, symbols, titles, art, and places of pilgrimage in various church regions across the globe demonstrates this phenomenon. This study investigates the portrayal of Mary at the Manggarai Catholic Church, which is situated in the Diocese of Ruteng, Flores. This study aimed to analyze the songs performed by Maria that are featured in the book “Dere Serani.” The central investigation focused on whether the depiction of Mary in songs is impacted by the representation of women in the local culture or not. This study utilized two main approaches, namely text content analysis and cultural studies. This study discovered that the depiction of Mary that is adopted by the local community extends beyond local perspectives and incorporates global viewpoints.